A Study on the Problems of Evil and Its Impact on Faith Among the Grade 12 Students in the Diocesan Catholic High Schools - Acero, John Christopher; Fernando, Daniel; Espartero, Reign Jedd; Ido, Vince Justin; Manongol, Mainard; Mariano, Mart; Mohong, Cleve Joshua; Talasero, Ronnie; Maniba, Sergio; Abutas, Marlene (Technium Social Sciences Journal, 2025)
This study assessed the degrees of perception of the problems of evil and its impact on faith among Grade 12 students in Diocesan Catholic High Schools. Additionally, it determined the differences and relationship between the problems of evil and the impact on faith when grouped according to their demographics. To assess these, the study employed a quantitative design, specifically descriptive-comparative, and correlational approaches. In data gathering, the study used a validated and reliability-tested researcher-made questionnaire, which was answered by 293 Grade 12 students during 2024-2025. Also, the respondents were determined using stratified random sampling. In analyzing the data, mean, standard deviation, Mann Whitney U, Kruskal Wallis, and Spearman rank correlation were utilized. Hence, the findings revealed that Grade 12 students have a strong perception of the problems of evil. Likewise, they experienced a strong impact on their faith because of a strong perception of evil. Moreover, there were no significant differences in the problem of evil relative to religion and family structure. However, there were significant differences in terms of sex, church ministry, and strand. Meanwhile, there were no significant differences in the impact on faith when grouped according to religion, strand, and family structure. However, there were significant differences relative to sex and church ministry. Lastly, there was a significant relationship between the degrees of the problems of evil and the degrees of impact on faith. The findings suggest that the schools may provide faith formation programs and spaces for theological discussions to support students in navigating the problems of evil. Also, the schools may encourage their students to actively participate in parish youth ministries, altar servers, or join the choir, as these activities may become meaningful avenues for deepening their faith amidst their strong perception of evil.